Testing and Analysis of Aluconcrete Beams - Bridle, R. J.; Roberts, T. M.; Uran, N.; A. Razak, A. K. (American Society of Civil Engineers (ASCE), 2007)
A series of four-point bending, quasi-static and high-cycle fatigue tests has been conducted on aluconcrete beams consisting of an aluminum extrusion acting compositely with a high-strength concrete infill. Observations and analysis of the quasi-static tests and test results indicate that fully effective composite action was maintained up to failure, with negligible or minimal slip occurring between the aluminum extrusion and high-strength concrete. Failure of the beams during the high-cycle fatigue tests resulted from a gradual degradation of the bond between the concrete and aluminum, resulting in noticeable slip and a corresponding reduction in composite action. Even so, the fatigue test beams, which had a shear bond transmission length of only 575mm, were able to sustain approximately one-quarter of a million load cycles from approximately 5 to 50% of their ultimate load.